A Quantitative Method for Determining Underground Garage Parking Comfort and Development of a BIM Based Analysis Program - Dejiang Wang; Chang Liu (Applied Sciences, 2022)
The current parking space design only considers whether the parking space size meets the requirements of the specification, but because of people’s parking habits, parking technology is different and its requirements for parking comfort are different, and so our parking space design should be people-oriented to meet people’s requirements for parking comfort. At present, the main dilemma faced by designers considering the comfort of parking is that it is difficult to quantify the comfort of parking. At the same time, the number of parking spaces in underground garages is large, so manual calculation of the comfort of parking is a huge task. Therefore, in this paper, we put forward the concept of parking comfort and put forward a calculation model that can quantify the parking comfort. Considering the position coordinates of the collision-prone parts in the whole process of vehicle parking, the collision position coordinates and site obstacle coordinates are established together to form the vehicle collision constraint relationship in the process of parking, so as to quantify parking comfort into specific values. At the same time, based on the calculation model and BIM secondary development technology, we develop a program for automatic calculation and detection of parking comfort based on the BIM model, so as to automatically evaluate the parking comfort of each parking space in the whole underground garage effectively, quickly, and accurately.